Cavity-ring-down spectroscopy of the heavy ozone isotopologue 18O3: Analysis of a high energy band near 95% of the dissociation threshold. (February 2022) - Vasilchenko, Semen; Barbe, Alain; Starikova, Evgeniya; Kassi, Samir; Mondelain, Didier; Campargue, Alain; Tyuterev, Vladimir
Highlights: Cavity ring down spectroscopy of 18 O3 between 7920 and 7985 cm −1 . 259 transitions assigned to 7ν1 +ν3 vibrational band. Upper vibrational state located a few% below the dissociation limit at 8620 cm −1 . Effective operator modeling of the spectra. Good agreement with ab initio values for the band center and rotational constants. Abstract: The absorption spectrum of the 18 O3 isotopologue of ozone was recorded by cavity-ring-down spectroscopy between 7920 and 7985 cm −1 with a routine noise equivalent absorption, αmin, on the order of a few 10 −11 cm −1 . This permitted to detect and analyze an extremely weak vibrational band assigned as 7ν1 +ν3 following predictions from the ab initio potential energy surface reported in J Chem Phys 2013;139:134307. This is the most excited rovibrational band of the 18 O3 isotopologue detected so far. In total, 259 ro-vibrational transitions were measured and modeled using an effective Hamiltonian model. The vibrational dipole transition moment parameter of the band deduced from the analysis and the fit to 177 experimental line intensities was evaluated as 2.6 × 10 −6 Debye. The absorption coefficient of the recorded pure 18 O3 spectrum was found significantly smaller compared to that of the 16 O3 in the same range. The set of 171 upper state energies experimentally determined cover the range from 92.6% (at J  = 1) to 97% (at J  = 26) of the first dissociation threshold D0 . The comparison with ab initio predictions for the band origin and ʋ-dependent rotational constants is discussed. An absorption line list containing 477 transitions is provided as Supplementary material for the 7ν1 +ν3 band.